ANALYSIS COMMUNITYâS COPING STRATEGIES AND LOCAL RISK GOVERNANCE FRAMEWORK IN RELATION TO LANDSLIDE: A Case of Tawangmangu Sub-District, Karanganyar Regency, Indonesia - , Heru Setiawan; , Dr. Dyah R Hizbaron, MT., M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Landslides were occurred in 2007 at Tawangmangu resulting collapse of dozens houses and killing of dozens people. Analysis of people perception and analysis of the coping strategy to landslides are the two elements that are essential to determine the level of preparedness of communities to landslides occurring in the future. People coping strategy should be implemented in line with the coping strategy conducted by the government and other stakeholders. To know the preparedness of government and other stakeholders in facing landslide, it was required to analysis the risk governance frame work. Analysis of risk governance frame work was done at the district and sub-district level. Survey method with random sampling was applied to assess the level of people perception and people coping strategy related to landslide. The number of respondents was spread proportionally across five villages